Walking the Line – The International Origins of Civil Aviation Regulation in Canada - Seyer, Sean (Scientia Canadensis, 2015)
This paper explores how international considerations shaped the Air Regulations of 1920, the first regulation of civil aviation in Canada. After the First World War Allied representatives drafted the Convention Relating to the Regulation of Aerial Navigation to both constrain the revolutionary potential of heavier-than-air flight and foster international civil aviation. The Borden government considered aviation regulation a domestic matter rather than an imperial one and recognized that Canada’s geographic position necessitated regulatory coordination with the United States. In response, it crafted a postwar aeronautical policy that allowed for regulatory compatibility with the convention, facilitated cross-border flight with the United States, and promoted a more independent foreign policy. Thus Canada’s postwar regulation of the airplane represents an important element in its larger twentieth-century realignment away from Great Britain and towards the United States.